2020
DOI: 10.3389/fimmu.2020.563402
|View full text |Cite
|
Sign up to set email alerts
|

CD4 and CD8 T Cell Memory Interactions Alter Innate Immunity and Organ Injury in the CLP Sepsis Model

Abstract: The role of T cell memory in sepsis is poorly understood. Recent work has demonstrated that mice exposed to frequent antigenic stimulation, in contrast to laboratory mice, better recapitulate the human T cell repertoire. This difference may profoundly alter responses to inflammatory insults. We induced isolated T cell memory by inoculating C57Bl/6 mice with an anti-CD3ϵ activating antibody, a process we term “immune education.” These mice were subjected to the cecal ligation and puncture (CLP) model of sepsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…In bovine bacteremia, angiotensin-II–treated animals displayed lower levels of both IL-6 and IL-10 versus vehicle-treated controls ( 27 ). In our study, mice that received angiotensin-II alone displayed no elevations in IFN-γ, a cytokine that we and others have shown to be an important mediator of tissue autoinjury in the acute response to systemic inflammatory stimulus ( 28 )( 29 ). One interpretation of the serum cytokine levels is that angiotensin-II alters the kinetics of the inflammatory response to CLP, initially augmenting and subsequently limiting systemic inflammation, promoting initial bacterial defense, and limiting subsequent collateral organ dysfunction.…”
Section: Discussionmentioning
confidence: 47%
“…In bovine bacteremia, angiotensin-II–treated animals displayed lower levels of both IL-6 and IL-10 versus vehicle-treated controls ( 27 ). In our study, mice that received angiotensin-II alone displayed no elevations in IFN-γ, a cytokine that we and others have shown to be an important mediator of tissue autoinjury in the acute response to systemic inflammatory stimulus ( 28 )( 29 ). One interpretation of the serum cytokine levels is that angiotensin-II alters the kinetics of the inflammatory response to CLP, initially augmenting and subsequently limiting systemic inflammation, promoting initial bacterial defense, and limiting subsequent collateral organ dysfunction.…”
Section: Discussionmentioning
confidence: 47%
“…showed that induced adaptive immune memory altered the magnitude of organ dysfunction following CLP. 1,34 The experiments described here identify one potential mechanism. These studies indicate that the combination of TCR-and TLR4-mediated effects on T cell and DC interactions altered the response to LPS-induced inflammation and cellular dysfunction.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, murine models of inflammatory disease may not appropriately reflect the role played by adaptive immunity 3,4 . Our recent work showed that induced adaptive immune memory altered the magnitude of organ dysfunction following CLP 1,34 . The experiments described here identify one potential mechanism.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations